Factors influencing consumer purchase decisions of Celcom prepaid plan at Bandar Baru Klang, Selangor / Juhari Musleh - Musleh, Juhari (Faculty of Business and Management, 2010)
Mobile phone has proven to be an integral part of the growth, development, success and efficiency of any business and economy. The past decade has seen enormous increase in mobile phone users, significant reduction in tariff and increase in talk time, usage of short message service (SMS) and various other mobile phone applications. It is popular due to its compact portability to suit the highly mobile lifestyle of today’s society. This study was held to find out whether all the four independent variables can influence the consumer purchase decision or not. Those four independent variables are product, price, promotion, and place. The result can be seen through the findings and interpretations of the report. The researcher wants to study what the factors influencing consumer purchase decision of Celcom prepaid plan. By understanding the factors that influencing consumer purchase decision, it will help this research to overcome the problem that facing by Celcom. It is important for the company to know which factors the most influencing customer to be used in order to enhance the increasing of purchase decision on Celcom prepaid plan. The result show that, promotion are higher percentage of factor influencing consumer purchase decisions compare to the others variables which are price, product and place. There are respondent who suggested that Celcom give more rewards to its loyal customers. The rewards may be in terms of free airtime credit. In other way, Celcom may also adopted how Maxis rewarding its loyal customer by giving points each time the customer reload their credit. The points are redeemable to into airtime credit.